IF Credit Rating Agencies Provide Inaccurate Analysis of Sovereign Nations, How can Business Schools Effectively Teach Financial Statement Reporting? (Global Journal of Management and Business Research, 2014)
Abstract not found
Keywords: cultural illiteracy; effective teaching